What Happened to Gender and History? - Deborah Thom (Revue Française de Civilisation Britannique)
The project of putting women into history has developed through women’s history into a substantial academic enterprise. Histories of women’s everyday lives and their political contribution have multiplied and professionalized. However the study of gender has turned more recently to men and masculinity which has become seen as more troubled and fragile in the process of historical rediscovery. The question of feminism and the universal or particular claims to rights remains and requires further research into multiple differences rather than the assumption that difference exists and raising the question of how far a history of inequality can ever abandon the issue of gender entirely. The question of class and sexuality raises new areas of historical discussion which are being met by extensive research into performance and practise. Gender history is not a unity in that some historians still believe in binary difference while others reject the notion of identity as productive. Gender history remains an exciting and expanding field of study and should become a pertinent site of enquiry in other specialised histories.